SOIL PHYTOREMEDIATION PLANTS AROUND US: POTENTIALS, MECHANISMS, AND APPLICATIONS FOR SUSTAINABLE ENVIRONMENTAL RECOVERY - Suwarniati, Suwarniati (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
Soil contamination caused by the accumulation of heavy metals, pesticides, and industrial waste has become a critical environmental problem that affects human health, agricultural productivity, and ecosystem stability. Phytoremediation is an eco-friendly approach that utilizes plants to improve soil quality through the absorption, stabilization, degradation, or volatilization of pollutants. This article explores the potential of commonly found plant species in the surrounding environment as phytoremediation agents, including their working mechanisms, key species, and ecological implications. A literature review (2015–2024) reveals that Vetiveria zizanioides, Phragmites australis, Cyperus rotundus, Helianthus annuus, and Ageratum conyzoides demonstrate significant capability in reducing concentrations of heavy metals such as Pb, Cd, Zn, and Cu, as well as pesticide residues in contaminated soils. These findings highlight the promising role of phytoremediation in supporting sustainable land rehabilitation, especially in regions where access to advanced remediation technology is limited.